Acceptance, Safety and Sustainability Recommendations for Efficient Deployment of UAM - Outline of H2020 CSA Project. Issue 1 (1st February 2022) - Dziugiel, B; Mazur, A; Stanczyk, A; Maczka, M; Liberacki, A; Di Vito, V; Menichino, A; Melo, S; ten Thije, J; Hesselink, H; Vreeken, J; Giannuzzi, M; et al.
Abstract: The vision of a third dimension added to hitherto nearly flat urban/metropolitan transport system gained the potential to become a mobility revolution for both logistics operators and, in the near future, for passengers as well. In spite of the expected emergence of this new form of transport and respective benefits for the efficiency of the mobility system at urban and suburban scale, UAM implementation also involves unprecedented and numerous challenges for cities and for all local public and private stakeholders. The local governing bodies are expected to provide policy, regulations and guidance for the implementation of UAM and to assure its integration with the ground mobility systems as well as with other urban functionalities. Taking into account both potential benefits and associated challenges related to UAM implementation, ASSURED-UAM (Acceptance, Safety and SUstainability Recommendations for Efficient Deployment of UAM) project, funded by the H2020 Programme, aims to support that effort, by providing a multidisciplinary study on operational and policy frameworks for the process of the introduction of unmanned modes of UAM.